2018
DOI: 10.1590/1980-5373-mr-2017-0655
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of Polycrystalline Mixed Copper-Zinc Ferrites

Abstract: Polycrystalline mixed Cu-Zn spinel ferrites with general formula Cu 1-x Zn x Fe 2 O 4 (x = 0.0, 0.1, 0.3, 0.5 and 0.7) have been prepared by solid-state reaction method. The effect of Zn 2+ ions on transport properties such as DC and AC resistivity, dielectric constant and dielectric loss tangent has been presented in this paper. The resistivity increases with Zn content and decreases with frequency which have been explained by Verway's hopping mechanism. Decrease of DC electrical resistivity with increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Akhteret. al., [14] estimated the real part of the dielectric constant (ε') and also dielectric loss (ε''), using the relation,…”
Section: 6observation Of Dielectric Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…Akhteret. al., [14] estimated the real part of the dielectric constant (ε') and also dielectric loss (ε''), using the relation,…”
Section: 6observation Of Dielectric Propertymentioning
confidence: 99%
“…This mechanism is observed in the present study. Results indicate that the interrelation dipoles have a reduced amount of time to orient themselves in the direction of the applied eld [14,32,33].…”
Section: Calculation Of Particle Sizementioning
confidence: 99%
“…The conduction phenomenon and dielectric polarization in ferrites can be attributed to the hopping of charges between a divalent cation (M 2+ ) and Fe 3+ . 15 When studying Mn 2+substituted cobalt ferrite, Atif et al concluded that the dielectric properties were strongly affected by both the distribution of cations mediated by Mn 2+ doping and the change in morphology associated with the increase in Mn 2+ content and its microstructure. 16 Kolekar et al deliberated that the hopping of polarons is responsible for the conductivity in Mn 2+ -substituted cobalt ferrite.…”
Section: Introductionmentioning
confidence: 99%
“…All these can be highly influenced by various parameters like doping, variation of sintering temperature, purity of the reactants etc. [1,2].…”
Section: Introductionmentioning
confidence: 99%